A Comparative Study of Bcl-2 Expression in Oral Leukoplakia with Dysplasia, Verrucous Carcinoma, and Oral Squamous Cell Carcinoma - Bireswar Roy; Shivani Saxena; Narayan Tripathi; Mridul Sharma; Deepmala Rana; N Pramukh; Miral Mehta (Journal of Pharmacy and Bioallied Sciences)
Aim: To study the immunohistochemical expression of Bcl-2 in oral leukoplakia with dysplasia, verrucous carcinoma and oral squamous cell carcinoma(OSCC). Methodology: A total of 80 formalin-fixed , paraffin- embedded specimens were selected , amongst them 30 cases of different grades of dysplasia- 10 mild, 10 moderate and 10 severe and 30 oral squamous cell carcinoma of various grades- 10 well differentiated, 10 moderately differentiated and 10 poorly differentiated, 10 verrucous carcinoma had been included in the study. 10 normal buccal mucosa were used as control group. Results: The immunohistochemical expression of Bcl-2 in oral leukoplakia with different grades of dysplasia, in verrucous carcinoma and in different grades of oral squamous cell carcinoma with normal mucosa were compared. Moreover, the expression of Bcl-2 was found to increase significantly between dysplasia and different grades of oral squamous cell carcinoma. Conclusion: The expression of Bcl-2 has always guided the researchers towards mapping the progression of dysplasia as well as malignant transformation at the molecular level.